Penerapan Aplikasi Classroom pada Mata Pelajaran Qur’an Hadits - Huda, Moh. Miftakhul; Az Zafi, Ashif (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2021)
E-learning is the use of learning media using the internet, to send a series of solutions that can increase knowledge and skills in using learning methods. In this study, the aim of this research is to determine the application of the classroom application in the Qur'an Hadith subject at MA NU Al Hidayah. This research also discusses the impact or factors related to the use of the classroom application. This research used a qualitative descriptive analysis type with the type of research in the form of field studies at the MA NU Al Hidayah School, followed by the data collection process, this study used documentation techniques and interviews with the teachers who taught the Qur'an Hadith subjects and some of their students. The research subjects were teachers of Qur'an Hadith subjects at MA NU Al Hidayah and some of their students. The research subjects were teachers of Qur'an Hadith subjects at MA NU Al Hidayah and some of their students. The results showed that: (1) this application is very influential in online learning. (2) there are obstacles that occur in learning. The effect of this research can overcome the obstacles that occur in ongoing learning or find new innovations for the future.